A Modified Miniscope System for Simultaneous Electrophysiology and Calcium Imaging in vivo - Wu, Xiaoting; Yang, Xiangyu; Song, Lulu; Wang, Yang; Li, Yamin; Liu, Yuanyuan; Yang, Xiaowei; Wang, Yijun; Pei, Weihua; Li, Weidong (Frontiers in Integrative Neuroscience, 2021)
The miniscope system is one of the calcium (Ca2+) imaging tools with small size and lightweight and can realize the deep-brain Ca2+ imaging not confined to the cerebral cortex. Combining Ca2+ imaging and electrophysiology recording has been an efficient method for extracting high temporal-spatial resolution signals in the brain. In this study, a particular electrode probe was developed and assembled on the imaging lens to modify the miniscope system. The electrode probe can be tightly integrated into the lens of the miniscope without increasing the volume, weight, and implantation complexity. In vivo tests verified that the proposed modified system has realized the simultaneous recording of Ca2+ signals and local field potential (LFP) signal in the hippocampus CA1 region of an adult mouse.